VD_FINDINFO HC / 2016 / 17 vom 11. Dezember 2015 - VD Tribunal cantonal (2015)
MESURE PROVISIONNELLE, GARDE ALTERNÉE, OBLIGATION D'ENTRETIEN, CONJOINT | 176 al. 3 CC, 273 al. 1 CC, 276 CC, 276 al. 1 CPC (CH)